Serotype distribution ofStreptococcus pneumoniain children with invasive disease in Turkey: 2015-2018 - (:unkn) unknown (TAYLOR & FRANCIS INC, 2020)
Objectives To determine the serotype distribution of pneumococcus causing invasive pneumococcal disease (meningitidis, bacteremia and empyema) in children in Turkey, and to observe potential changes in this distribution in time to guide effective vaccine strategies. Methods We surveyedS. pneumoniaewith conventional bacteriological techniques and with real-time polymerase chain reaction (RT-PCR) in samples of cerebrospinal fluid (CSF), blood and pleural fluid.S. pneumoniaestrains were isolated from 33 different hospitals in Turkey, which are giving health services to approximately 60% of the Turkish population. Results A total of 167 cases were diagnosed with invasive pneumococcal disease between 2015 and 2018. We diagnosed 52 (31.1%) patients with meningitis, 104 (62.2%) patients with bacteremia, and 11 (6.6%) patients with empyema. Thirty-three percent of them were less than 2 years old and 56% less than 5 years old. Overall PCV13 serotypes accounted for 56.2% (94/167). The most common serotypes were 19 F (11.9%), 1 (10.7%) and 3 (10.1%). Conclusions Besides the increasing frequency of non-vaccine serotypes, vaccine serotypes continue to be a problem for Turkey despite routine and high-rate vaccination with PCV13 and significant reduction reported for the incidence of IPD in young children. Since new candidate pneumococcal conjugate vaccines with more serotype antigens are being developed, continuing IPD surveillance is a significant source of information for decision-making processes on pneumococcal vaccination.
Keywords: Epidemiology; serotypes; streptococcus pneumonia; surveillance; Turkey; PNEUMOCOCCAL CONJUGATE VACCINE; INFLUENZAE TYPE-B; STREPTOCOCCUS-PNEUMONIAE; EMPYEMA; IMPACT; EPIDEMIOLOGY; 7-VALENT; FAILURES